1981
DOI: 10.1073/pnas.78.2.1255
|View full text |Cite
|
Sign up to set email alerts
|

Enkephalin-like immunoreactivity of olivocochlear nerve fibers in cochlea of guinea pig and cat

Abstract: The distribution ofenkephalin-like immunoreactivity in the cochlea ofthe guinea pig and cat was studied. Indirect immunofluorescence immunohistochemistry using antisera generated against a methionine enkephalin-bovine thyroglobulin conjugate was applied to surface preparations of the organ of Corti and cryostat sections of the whole of the cochlea. In the cochlear osseous spiral lamina, immunofluorescence was localized to unmyelinated fibers ofthe intraganglionic spiral bundle. In the organ of Corti, immunoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 42 publications
(77 reference statements)
3
24
0
1
Order By: Relevance
“…The ¢rst indirect evidence that suggested an association of enkephalin with the olivocochlear system was made using guinea pig as an experimental animal (Fex and Altschuler, 1981). These authors already suggested that enkephalin could be involved in both the LOC and the medial olivocochlear system (MOC).…”
Section: Speculations Of the Functional Roles Of Met 8 In The Auditormentioning
confidence: 99%
See 1 more Smart Citation
“…The ¢rst indirect evidence that suggested an association of enkephalin with the olivocochlear system was made using guinea pig as an experimental animal (Fex and Altschuler, 1981). These authors already suggested that enkephalin could be involved in both the LOC and the medial olivocochlear system (MOC).…”
Section: Speculations Of the Functional Roles Of Met 8 In The Auditormentioning
confidence: 99%
“…Neurons in the cochlear nucleus give rise to a number of parallel ascending pathways that are involved in the processing of di¡erent properties (monaural, binaural, temporal and spectral) of the auditory stimulus (for reviews see Malmierca, 2003;Malmierca and Mercha ¤n, 2004). The ¢rst report on enkephalin immunostaining in the auditory system by Fex and Altschuler (1981) was made in guinea pig. This study ¢rst showed the potential involvement of enkephalin in the modulation of the cochlea through the descending olivocochlear system.…”
Section: Introductionmentioning
confidence: 99%
“…The opposite effects of ACh suggest the existence of two types of receptors for ACh, muscarinic-like and nicotinic-like receptors. Considering the fact that ACh frequently co-localizes with neuropeptides in the cochlear efferent neurons, the latter are viewed as neuromodulators [9][10][11][12]. Recently, such a co-localization has been proposed for efferent vestibular system as well [1].…”
Section: Introductionmentioning
confidence: 99%
“…Las encefalinas fueron descritas en el cerebro desde mediados de los años 70 18 , pero caracterizadas en el sistema eferente auditivo una década después 29 . Se postula que las encefalinas tienen funciones inhibitorias dentro del sistema auditivo de mamíferos, rol funcional que ha sido constatado de manera indirecta a través de la verificación del aumento de su concentración en ambientes ruidosos y disminución en ambientes silenciosos 16 .…”
Section: Opioides Y Prgc (Ocl)unclassified